PERMANENT MAGNET MOTOR PERFORMANCE TO ENLONG PRODUCTION PERION FOR ELECTRIC SUBMERSIBLE PUMP - Andreas Setyabudi (Prosiding Seminar Nasional Pakar, 2020)
There are some lost energy by using ordinary motor as we called Asynchronous Motor. By using Permanent Magnet Motor as new technology in Electric Submersible pump. There are some advantages by using Permanent Magnet Motor which can help to improve efficiency and consume less energy, therefore can give more profit in long period of production. These advantages consists of durability for motor, consume less electricity energy to maintain, give bigger production rate, reduce mistiming, and longer life time than Asynchronous Motor. By implementation of Permanent Magnet motor in oil and gas industry can be new revolution step to face the new future.